1969
DOI: 10.1002/jsfa.2740200715
|View full text |Cite
|
Sign up to set email alerts
|

Purothionin analogues from barley flour

Abstract: Acid treatment of a light‐petroleum extract of barley flour yielded two proteins (termed hordothionins) closely similar in electrophoretic behaviour to the purqthionin doublet obtained from wheat by the same procedure. The major (faster) component, hordothionin a has been obtained apparently pure. Comparison of its amino acid composition, peptide maps, immunological reactions and C‐terminal end group with those of purothionin a has confirmed the relationship between the proteins from the two genera although so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

1969
1969
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 9 publications
1
35
0
Order By: Relevance
“…The nsLTPs from wheat and maize seeds were kindly provided by Dr. Didier Marion (Institut National de Ia Recherche Agronomique, Nantes, France), and the nsLTP from radish was purified as described by Terras et al (1992a). Ac-AMP1 was isolated from amaranth seeds as described by Broekaert et al (1992), and P-purothionin was purified from wheat flour by the method of Redman and Fisher (1969).…”
Section: Methodsmentioning
confidence: 99%
“…The nsLTPs from wheat and maize seeds were kindly provided by Dr. Didier Marion (Institut National de Ia Recherche Agronomique, Nantes, France), and the nsLTP from radish was purified as described by Terras et al (1992a). Ac-AMP1 was isolated from amaranth seeds as described by Broekaert et al (1992), and P-purothionin was purified from wheat flour by the method of Redman and Fisher (1969).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the multiple-alignment criteria of Feng & Doolittle (1987), all the available thionin amino acid sequences were classified into four well-defined structural types (I to IV, García-Olmedo et al, 1989, two of which were present in the cereals wheat and barley. Type I corresponds to the original purothionins from wheat flour (Balls et al, 1942a,b), which were later characterized in barley endosperm (Redman & Fisher, 1969), and type II is represented by thionins first isolated from the leaves of the parasitic plant Pyrularía púbera (Vernon et al, 1985) and then identified in those of barley (Bohlman & Apel, 1987;Gausing, 1987). Types III and IV respectively include the viscotoxins from mistletoes and the crambins from the Abyssinian cabbage (see García-Olmedo et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Thionins were first identified as a group of low molecular weight proteins in the organic solvent-extractable fraction of wheat and barley flour (1,2). The purified proteins were subsequently found to kill microorganisms (3).…”
mentioning
confidence: 99%